Manajemen Kepala Sekolah dalam Pengelolaan Anggaran Pendapatan dan Belanja Sekolah SMA Negeri 10 Tanjung Jabung Timur - Maria Hastuti; Martinis Yamin; Lukman Hakim (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2018)
This study aims to examine the management of the Principal towards the school's income and expenditure budget (APBS) at Public High School or SMAN 10 East Tanjung Jabung, Jambi. The research was motivated by 1) APBS planning carried out by the Principal was only formulated by school managerial decision makers, was not discussed openly with all existing human resources, 2) there was still limited training by the Principal regarding the preparation of the APBS, 3) Principals had difficulty adjusting the APBS plan with needs, and 4) the assessment of the implementation of the APBS is not effective. This research uses qualitative methods that are based on the philosophy of postpositivism. Data is obtained through participation observation, interviews, and documentation. Based on the research, it is known that the sources and budget allocations are still limited. there are still problems with the process, namely: a) Still difficult for budget users to specify budget requirements, b) The ability of administrative personnel to manage BOS is limited, c) school budget allocation as a source of school development is still not in accordance with the real needs of schools and d) Limitations of school principals carry out continuous monitoring. Planning activities are still not detailed, the implementation has been carried out in accordance with the planning, and the APBS evaluation has been carried out effectively.